2022
DOI: 10.3390/ijerph19031496
|View full text |Cite
|
Sign up to set email alerts
|

Internal Quality and Job Satisfaction in Health Care Services

Abstract: (1) Background: The main purpose of this study was to evaluate the health services’ internal quality level in Greek public hospitals and to investigate whether there is a relation between internal quality and health care professionals’ job satisfaction. (2) Material and Methods: A cross-sectional study was conducted in six public hospitals (four general and two specialized hospitals). The following tools were used to collect data: (a) the SERVQUAL questionnaire, which is designed to measure service quality thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 71 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…In summary, the public sector can obtain organizational commitment from its employees through the promotion of ethical competence. Obtaining employee commitment, in turn, tends to make them feel more satisfied, favoring the emergence of desirable effects, such as a positive perception of the workplace (Goula et al ., 2022) and increased job performance (Demircioglu, 2023).…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the public sector can obtain organizational commitment from its employees through the promotion of ethical competence. Obtaining employee commitment, in turn, tends to make them feel more satisfied, favoring the emergence of desirable effects, such as a positive perception of the workplace (Goula et al ., 2022) and increased job performance (Demircioglu, 2023).…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…Additionally, job satisfaction is defined as an emotional state of pleasure that results from an employee’s experiences and understanding of their job (Awan et al ., 2020). In a study conducted in the Greek public sector, a direct relationship was found between employee job satisfaction and a positive perception of the internal quality of the workplace (Goula et al ., 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Thus, nursing directors should know the various impacts of the different nursing models (Rantanen et al, 2016). Positive correlation between the job satisfaction and the quality dimensions has been perceived in hospitals (Goula et al 2022). Founding a sense of confidence between management and health professionals through successful communication, transparent evaluation, and reward is important to improving an internal quality culture in hospitals (Goula et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Positive correlation between the job satisfaction and the quality dimensions has been perceived in hospitals (Goula et al 2022). Founding a sense of confidence between management and health professionals through successful communication, transparent evaluation, and reward is important to improving an internal quality culture in hospitals (Goula et al, 2022). Schmenner and Swink (1998) presents the theory of swift and even flow on which the swifter and more even the flow of materials through an activity chain, the more productivity that chain is.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, studies have shown that both work stress and patient-physician con ict can affect the clinical performance of residents (Hou et al, 2020). In addition, higher work satisfaction is associated with better quality of healthcare (Goula et al, 2022), lower burnout (Li et al, 2020), and lower job turnover (Ofei-Dodoo et al, 2020). In summary, work-related perception is a key predictor of clinical performance among residents (H3).…”
Section: Introductionmentioning
confidence: 99%